PENGARUH UKURAN PERUSAHAAN, MODAL INTELEKTUAL DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SUB SEKTOR LOGAM YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2010 - 2014 - Stella Tandean (JURNAL MUTIARA AKUNTANSI, 2017)
The great total assets showed the company experienced growth in financial performance. In addition, such non-material wealth of knowledge, copyrights, patents, human resources support the success of the company's performance. Each company has a born significant operational cost, so the company needs funds from outside. The financial performance was assessed using profitability. A company is considered if its profit is achieved with good management within the company. The method of the study is a quantitative method, this type of research is descriptive with the samples of 40 companies drawn through a purposive sampling method. Data collection was performed by documentation through secondary data sources. The nature of research is associative expalanatory. The data analysis used is multiple linear regression analysis using the F-test and T- test at significance level of 5% and Adjusted R-square value of 0.765 or 76% of the variables of firm size, intellectual capital and leverage variables can explain the dependent variables. The results of the research on the hypothesis indicates that the size of the company, intellectual capital and leverage simultaneously have a significant and positive effect on the financial performance by 43.2%. Partially, the size of the company with a value of 0,010 does not have a significant and positive effect on financial performance. While intellectual capital with a value of 0.159 has a positive and significant effect on financial performance and the value of leverage -0.106 has a significant negative effect on financial performance.Keywords: Company Size, Intellectual Capital, Leverage, Financial Performance